Vaccine shot-limiting: Estimating the prevalence, indicators, and impact on vaccination status — Michigan, 2012. Issue 7 (15th February 2017) - Weinberg, Meghan; Dietz, Stephanie; Potter, Rachel; Swanson, Robert; Miller, Corinne; McFadden, Jevon
Highlights: Timely vaccination is required for full protection from vaccine-preventable diseases. Certain parents limit the number of shots their child receives per vaccination visit. These mothers are more likely to be white, college graduate, and married. Shot-limited children are more likely to have a midwife birth attendant. Shot-limited children are less likely to be up-to-date on vaccinations by 24 months. Abstract: Background: Concerns regarding vaccine safety and pain have prompted certain parents to limit the number of shots their child receives per visit. We estimated the prevalence of shot-limited children in Michigan, described their characteristics, assessed whether shot-limited children were up-to-date on recommended vaccinations, and investigated possible intervention points for vaccination education. Methods: We analyzed vaccination registry and birth record data of children born in Michigan during 2012 who had ⩾2 vaccination visits, with ⩾1 visits after age 5 months. Shot-limited was defined as receiving ⩽2 shots at all visits through age 24 months. Nonlimited children received >2 shots at ⩾1 visits. Up-to-date vaccination was based on receipt of a seven-vaccine series and was determined at ages 24 months and 35 months. Risk ratios (RR) were calculated using risk regression. Results: Of 101, 443 children, a total of 2, 967 (3%) children were shot-limited. Mothers of shot-limited children were more likely to be white (RR: 1.2; 95% confidence interval [CI]: 1.2–1.2), college graduate (RR: 1.9; 95% CI: 1.9–2.0), and married (RR: 1.5; 95% CI: 1.5–1.5). Compared with nonlimited children, shot-limited children were more likely to be born in a nonhospital setting (RR: 11.7; 95% CI: 9.4–14.6) and have a midwife attendant (RR: 1.9; 95% CI: 1.7–2.1). Shot-limited children were less likely to be up-to-date on recommended vaccinations (RR: 0.2; 95% CI: 0.2–0.3); this association was stronger for those with a midwife birth attendant (RR: 0.1; 95% CI: 0.1–0.2) rather than a medical doctor (RR: 0.3; 95% CI: 0.2–0.3). Conclusions: Shot-limited children are less likely to be up-to-date on vaccinations, possibly leading to increased risk for vaccine-preventable diseases. This association was stronger for those with a midwife birth attendant. This analysis should prompt targeted education, such as to midwives, concerning risks associated with shot-limiting behavior.